2012
DOI: 10.1186/1471-2458-12-773
|View full text |Cite
|
Sign up to set email alerts
|

Oral health conditions and frailty in Mexican community-dwelling elderly: a cross sectional analysis

Abstract: BackgroundOral health is an important component of general well-being for the elderly. Oral health-related problems include loss of teeth, nonfunctional removable dental prostheses, lesions of the oral mucosa, periodontitis, and root caries. They affect food selection, speaking ability, mastication, social relations, and quality of life. Frailty is a geriatric syndrome that confers vulnerability to negative health-related outcomes. The association between oral health and frailty has not been explored thoroughl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
168
3
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(185 citation statements)
references
References 49 publications
6
168
3
8
Order By: Relevance
“…Self‐assessed masticatory ability was associated with handgrip strength, although one study did not find an association between number of chewable foods and grip strength after adjustment for various confounders, although it reported an association between this oral health measure and other physical fitness assessment methods. In addition, the chewing surface (defined as the maximum number of intact functional units adjacent to each other) did not predict weight loss, and chewing problems were not associated with frailty …”
Section: Resultsmentioning
confidence: 96%
“…Self‐assessed masticatory ability was associated with handgrip strength, although one study did not find an association between number of chewable foods and grip strength after adjustment for various confounders, although it reported an association between this oral health measure and other physical fitness assessment methods. In addition, the chewing surface (defined as the maximum number of intact functional units adjacent to each other) did not predict weight loss, and chewing problems were not associated with frailty …”
Section: Resultsmentioning
confidence: 96%
“…Nevertheless, it's unusual for people to identify oral health conditions as their only health problems when those issues are so advanced that they affect feeding ability, speaking, chewing, physical appearance, and social life, frequently producing pain and favoring depression [1][2][3][4]. Oral health expectations among the elderly could also be influenced by age, education level, socioeconomic situation, and social support [3].…”
Section: Introductionmentioning
confidence: 99%
“…Oral health expectations among the elderly could also be influenced by age, education level, socioeconomic situation, and social support [3].…”
Section: Introductionmentioning
confidence: 99%
“…15 Andrade et al carried out a cross-sectional study among 1,374 community-dwelling older people in São Paulo, Brazil, and they reported that number of teeth was inversely correlated with likelihood of frailty. In one such study, Castrejón-Pérez et al analyzed the relationship between physical frailty and oral health problems in 699 individuals aged ≥70 years living in Mexico City.…”
Section: Explanationmentioning
confidence: 99%